Identification of circulating metabolites associated with chronic rhinosinusitis using Mendelian randomization analysis - Fan Jiang; Junhao Tu; Wenqi Luo; Yizhen Jia; Qing Luo; Jing Ye (Brazilian Journal of Otorhinolaryngology)
Objective: This study aims to employ Mendelian Randomization (MR) analysis to investigate causal relationships between serum metabolites and CRS, identifying key pathogenic and protective factors and analyzing their mechanisms of action. Methods: Utilizing data from the Genome-Wide Association Studies (GWAS) database, employing two-sample MR analysis to investigate the potential causal relationship between 233 circulating metabolites with the occurrence of CRS. Inverse Variance Weighted (IVW) model, MR-Egger method, Weighted Median, and Weighted model were employed. Sensitivity analyses were conducted with Bonferroni correction. This research aims to elucidate the impact of metabolites on the development and progression of CRS, providing valuable insights into the underlying mechanisms. Results: Following MR analysis, two metabolites were significantly associated with CRS: Tyrosine (OR = 1.223; 95% CI 1.115–1.341; p = 1.96E-05) and Creatinine (OR = 1.208; 95% CI 1.103–1.322; p = 4.11E-05). These two key risk factors may be further studied for their pathogenesis and could be targeted for modulation in the treatment of CRS. However, there are several protective factors also worth exploring, among which the correlation is more significant: Ratio of conjugated linoleic acid to total fatty acids (OR = 0.809; 95% CI 0.708‒0.923; p = 1.73E-03), Albumin (OR = 0.787; 95% CI 0.670‒0.926; p = 3.76E-03),Conjugated linoleic acid (OR = 0.664; 95% CI 0.491‒0.898; p = 7.85E-03), Diacylglycerol (OR = 0.804; 95% CI 0.654‒0.989; p = 3.87E-02), Apolipoprotein A–I (OR = 0.915; 95% CI 0.845‒0.991; p = 2.89E-02). Conclusion: In our MR study, we discovered 28 circulating metabolites linked to CRS. Importantly, tyrosine and creatinine were identified as the most significant contributors to the pathogenesis of CRS, highlighting their potential as therapeutic targets. Additionally, several protective factors may offer new avenues for preventive strategies and therapeutic interventions. These findings underscore the clinical relevance of targeting these metabolites to modulate CRS progression and improve patient outcomes. Level of evidence: Level 2*.1